PELATIHAN PENGEMBANGAN BUM DESA (E-COMMERCE) DI KECAMATAN KARANGPAWITAN, KABUPATEN GARUT - Boris Paedefo Pakpahan (Politeknik Negeri Sriwijaya, 2022)
This study aims to describe the process of implementing the training program by Balai Besar Pelatihan dan Pemberdayaan Masyarakat Desa, Daerah Tertinggal dan Transmigrasi Jakarta. This research using a qualitative approach and using evaluative research methods to evaluate the process of implementing training activities. Based on this research, the evaluation on the implementation of the training includes the evaluation of the facilitators, participants to the committee or training organizers. The results of the evaluation will determine whether the facilitators, participants to the committee or training organizers have met the criteria in the training. The results of the training evaluation will be used as a guide in improving the implementation of training in the future.